Shear wall modeling with asymmetric openings by macro elements. (February 2021) - Mortazavi, Seyed Mohammad Reza; Zaeimdar, Behrouz
Abstract: In this study MVLEM (Multiple Vertical Line Element Model) is utilized to model a shear wall made of concrete with asymmetric openings. For this aim, an experimental RC shear wall with asymmetric openings was studied and modeled by the 3D microscopic FEM (Finite Element Method) via ABAQUS software package. To achieve a macroscopic model with a high accuracy two macroscopic shear walls were modeled. These macroscopic walls are identical whereas the main difference is the stiffness in the beam at the connection zone. The macroscopic modeling for different members of the studied concrete shear wall column next to the openings coupling beams and the wall is developed by horizontal and vertical springs that simulate shear and flexural behaviors. Modeling of these parts depends on the moment distribution from horizontal loading. Responses of the macroscopic models under static cyclic and monotonic loading were compared with the validated microscopic model. According to the results the proposed macroscopic model in which low connection stiffness was used shows acceptable accuracy with the microscopic model.